Contemporary issues in primary amenorrhea: An experience from a Tertiary Care Center - Bhuyan, Ashok Krishna (Medknow Publications & Media Pvt Ltd, 2012)
INTRODUCTION: Amenorrhea is classified as primary if menstrual bleeding has never occurred in the absence of hormonal treatment. The clinical significance of a lack of regular menstrual cycles extends beyond reproductive concerns. Episodes of amenorrhea as short as 90 day may have implications for bone and cardiovascular health. AIMS AND OBJECTIVE: To evaluate all patients presenting with primary amenorrhea in the Endocrinology OPD of Gauhati Medical College and Hospital. MATERIALS AND METHODS: A total of 14 patients presenting to the Endocrinology OPD from March 2010 to May 2012 with a history of primary amenorrhea were included in the study. All patients were subjected to a detailed history, a thorough clinical examination, and relevant biochemical, hormonal, and radiological investigations. RESULT: In our study, the average age of presentation was 17.23 ± 4.2 years. Out of the 14 patients presenting with primary amenorrhea, 5 patients (35.71%) were found to have Turner′s syndrome, 2 (14.28%) had XX (pure) gonadal dysgenesis, 2 (14.28%) patients had XY gonadal dysgenesis (Swyer syndrome), 2 (14.28%) patients had Müllerian agenesis, 2 (14.28%) patients had hypothalamic amenorrhea, and 1 (7.14%) patient was found to have multiple pituitary hormone deficiency. CONCLUSION: In concordance with other studies, Turner′s syndrome, Müllerian agenesis, and gonadal dysgenesis are the commonest causes of primary amenorrhea in our study. However, in contrast to certain Western reports, primary amenorrhea rather than short stature remains the commonest cause for seeking medical evaluation in patients with Turner′s syndrome.